Piperaquine concentration and malaria treatment outcomes in Ugandan children treated for severe malaria with intravenous Artesunate or quinine plus Dihydroartemisinin-Piperaquine - Byakika-Kibwika, Pauline; Ssenyonga, Ronald; Lamorde, Mohammed; Blessborn, Daniel; Tarning, Joel (BMC infectious diseases, 2019)
Treatment for severe malaria must be prompt with effective parenteral antimalarial drugs for at least 24 h to achieve fast parasite clearance, and when the patient can tolerate oral therapy, treatment should be completed with effective artemisinin based combination therapy (ACT) for complete parasite clearance and to prevent recrudescence. We evaluated piperaquine concentration and malaria treatment outcomes among Ugandan children treated for severe malaria with intravenous artesunate (AS) or quinine (QN) plus dihydroartemisininpiperaquine (DP), in Tororo District Hospital in Eastern Uganda.
Keywords: Piperaquine; Pharmacokinetics; Malaria; Children